IMPLEMENTASI METODE BERCERITA DALAM MENGEMBANGKAN EMPATI ANAK USIA DINI USIA 5-6 TAHUN - Arinah; Ihlas, Ihlas; Muslimin, Muslimin; Roshandel, Heshmat (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2025)
The background of this research focuses on the importance of developing empathy in early childhood as part of fundamental social skills. The purpose of this study is to determine the effectiveness of the storytelling method in developing empathy in early childhood 5-6 years by looking at how stories can build emotional understanding, improve the ability to recognize the feelings of others and encourage prosocial behavior in children's daily interactions. The method used in this research is qualitative research with a case study approach that aims to explore the implementation of the storytelling method in more depth. The data collection techniques used include observation, interviews, and documentation. The data sources were teachers and children involved in storytelling activities at Bani Insan Rabakodo Kindergarten. The data obtained were analyzed using qualitative data analysis techniques with a descriptive approach to describe the implementation process of the storytelling method and its impact on children's empathy development. The results showed that the implementation of the storytelling method at Bani Insan Rabakodo Kindergarten was effective in developing empathy in early childhood. Some of the activities carried out to support this process include the selection of stories relevant to empathy development, interactive and participatory storytelling, the use of visual media and puppets, and role-playing activities. All of these activities not only help children understand and feel the feelings of the characters in the story, but also improve their ability to show empathy towards others in everyday life. Research shows that the storytelling method is effective in developing empathy in children aged 5-6 years. Children are better able to understand the feelings of others and show a caring attitude. The implications of this research encourage educators and parents to use stories as a strategic approach in early childhood social-emotional learning.